Dating violence in young women from Coahuila - Pérez Pedraza, Bárbara de los Angeles (2021)
Dating violence is a social problem that mostly affects adolescent and young women, who experience different types of violence from their partner at all levels, and on many occasions neither aggressors nor victims recognize that what they are experiencing is violence, as they just consider it a usual way of relating to each other. A comparative correlational study was designed to compare the types of dating violence experienced by women who currently have a partner and by those who do not have one, and to relate the types of dating violence. Through convenience sampling, 208 women between the ages of 14 and 18 from Coahuila, Mexico were selected and administered the Partner Violence, Social Capital and Associated Thoughts questionnaire. The  results showed a high prevalence of physical and psychological violence during the dating period. Significant differences were found (p < 0.05), where women who currently have a partner suffered greater physical and economic violence than those who do not currently have a partner. Finally, a positive correlation was found between these two types of violence.